Detection of polycyclic aromatic hydrocarbon-DNA adducts in human lung. - Weston, A (1993)
Synchronous fluorescence spectroscopy has been combined with immunoaffinity chromatography (IAC) and HPLC to detect polycyclic aromatic hydrocarbon (PAH)-DNA adducts and measure r-7,t-8-dihydroxy-t-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BPDE)-DNA adducts in human tissues and cells. A monoclonal antibody (8E11) that recognizes a range of PAH-DNA adducts, but not chemically unrelated adducts, was used to prepare IAC columns. Samples of DNA (25 from human lung and 8 positive and negative controls) were hydrolyzed enzymically and subjected to IAC. Adducts captured by the antibodies and eluted in NaOH (50 mM) were analyzed for fluorescent properties. The spectral fluorescence excitation-emission matrices suggested the presence of mixtures of PAH-DNA adducts in some of the eluates. The eluates were subsequently hydrolyzed with acid (HCl, 0.1 N, 3 hr) and reanalyzed by synchronous fluorescence spectroscopy using a wavelength differential of 34 nm. In 6 of the 25 human lung DNA samples, materials with HPLC retention times identical to benzo[a]pyrene-7,10/8,9-tetrahydrotetrol were found to have fluorescence characteristics indistinguishable from pyrene. Comparisons with appropriate standards indicated that BPDE-DNA adduct levels were between 1 and 40 adducts in 10(8) unmodified nucleotides. No correlation was observed between lung DNA-adduct levels and measures of recent smoking (serum cotinine), but tissue samples taken from different portions of the same lungs showed variation in the DNA adduct levels detected. This finding complicates interpretation of the data and has important implications for the design of future experiments.